Variations in frequencies of drug resistance in Plasmodium falciparum - Rathod, Pradipsinh K. (The National Academy of Sciences of the USA, 1997)
Continual exposure of malarial parasite populations to different drugs may have selected not only for resistance to individual drugs but also for genetic traits that favor initiation of resistance to novel unrelated antimalarials. To test this hypothesis, different Plasmodium falciparum clones having varying numbers of preexisting resistance mechanisms were treated with two new antimalarial agents: 5-fluoroorotate and atovaquone. All parasite populations were equally susceptible in small numbers. However, when large populations of these clones were challenged with either of the two compounds, significant variations in frequencies of resistance became apparent. On one extreme, clone D6 from West Africa, which was sensitive to all traditional antimalarial agents, failed to develop resistance under simple nonmutagenic conditions in vitro. In sharp contrast, the Indochina clone W2, which was known to be resistant to all traditional antimalarial drugs, independently acquired resistance to both new compounds as much as a 1,000 times more frequently than D6. Additional clones that were resistant to some (but not all) traditional antimalarial agents acquired resistance to atovaquone at high frequency, but not to 5-fluoroorotate. These findings were unexpected and surprising based on current views of the evolution of drug resistance in P. falciparum populations. Such new phenotypes, named accelerated resistance to multiple drugs (ARMD), raise important questions about the genetic and biochemical mechanisms related to the initiation of drug resistance in malarial parasites. Some potential mechanisms underlying ARMD phenotypes have public health implications that are ominous.